PENENTUAN PRIORITAS PENANGANAN LOKASI KUMUH PERKOTAAN DI KOTA PAGAR ALAM - Didi Ardiansyah (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2022)
Slum area in Pagar Alam City covering an area of ​​63.58 hectares, slum areas such as houses or community housing conditions in the area are not appropriate or not in accordance with the standards applied, namely the standard for infrastructure and facilities needs, requirements for healthy houses, open space, building density, completeness of social facilities and others. This research method is a quantitative descriptive study that describes data about the level of slums with scoring analysis for non-physical and physical matters. Data collection methods are surveys, interviews and questionnaires about plans to improve the quality of the slum settlement environment. How to identify the level of slums by assigning a score to the slum indicator criteria according to a rating scale that can have an impact on slum areas in Pagar Alam City. The next step is to analyze the classification of the slum level in Pagar Alam City. The results obtained from the research are the characteristics of slum settlements in Pagar Alam City, which can be seen from the respective kelurahan indicated as slums including Sidorejo Village, Tebat Giri Indah, Beringin Jaya, Tumbak Ulas, Besemah Serasan, Bangun Jaya, Pagar Alam, Sukorejo, and Nendagung. Slum areas can be identified according to the condition of the building, service and management of drinking water, road conditions, waste water management, drainage conditions in the environment, waste conditions in the environment, fire alertness, land legality and other considerations. Besemah Serasan, while the areas classified as moderate slums are Sukorejo, Sidorejo and Tebat Giri Indah Villages. Overall, the high population density, lack of drinking water management, poor sanitation conditions, and solid waste conditions are one of the characteristics of slum areas in the area. The priority for handling areas that are included in the medium slum category is rejuvenation, while the severe slum category is rejuvenation and restoration.